THE INFLUENCE OF OBESITY AND AMBIENT TEMPERATURE ON PHYSIOLOGICAL AND OXIDATIVE RESPONSES TO SUBMAXIMAL EXERCISE - N. Ahn; K. Kim (Termedia Publishing House, 2014)
This study investigated the effects of obesity and ambient temperature on physiological responses and markers of oxidative stress to submaximal exercise in obese and lean people. Sixteen healthy males were divided into an obese group (n=8, %fat: 27.00±3.00%) and a lean group (n=8, %fat: 13.85±2.45%). Study variables were measured during a 60 min submaximal exercise test at 60% VO2max in a neutral (21±1°C) and a cold (4±1°C) environment. Heart rate, blood lactate, rectal temperature, serum levels of malondialdehyde (MDA) and superoxide dismutase (SOD) were measured at rest, during exercise and in recovery. Heart rate of both groups was significantly lower (P<0.05) in the cold than the warm environment, but there were no significant differences between the two groups. Serum SOD activity increased to a significantly greater extent (P<0.05) in the cold than the neutral environment, and remained elevated for longer during exercise in the obese group than the lean group. Serum MDA level during submaximal exercise was not significantly different between conditions or groups. Cold stress in exercise may challenge antioxidant defence mechanisms in obese subjects, but lipid peroxidation remains unchanged.